2014
DOI: 10.2471/blt.13.134809
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diarrhoeal deaths in seven low- and middle-income countries

Abstract: ObjectiveTo investigate the clinical characteristics of children who died from diarrhoea in low- and middle-income countries, such as the duration of diarrhoea, comorbid conditions, care-seeking behaviour and oral rehydration therapy use.MethodsThe study included verbal autopsy data on children who died from diarrhoea between 2000 and 2012 at seven sites in Bangladesh, Ethiopia, Ghana, India, Pakistan, Uganda and the United Republic of Tanzania, respectively. Data came from demographic surveillance sites, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 12 publications
2
50
0
3
Order By: Relevance
“…Similarly, reductions in child mortality (and especially from diarrhoeal diseases) have been notable, but while there have been major gains in use of oral rehydration therapy, care seeking for childhood pneumonia is low and rates of childhood undernutrition are still high. 44 Investments in social determinants and non-health sectors such as education, especially girls' education and female empowerment to reduce early marriages and high fertility rates, as well as effective communication strategies are likely to be especially important to improve and sustain gains in maternal and child health.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reductions in child mortality (and especially from diarrhoeal diseases) have been notable, but while there have been major gains in use of oral rehydration therapy, care seeking for childhood pneumonia is low and rates of childhood undernutrition are still high. 44 Investments in social determinants and non-health sectors such as education, especially girls' education and female empowerment to reduce early marriages and high fertility rates, as well as effective communication strategies are likely to be especially important to improve and sustain gains in maternal and child health.…”
Section: Discussionmentioning
confidence: 99%
“…It was further revealed that at six of the seven study sites, 70-100% of children with persistent diarrhea who died had been seen in a health-care facility, while more than 50% of them had received oral rehydration solutions or intravenous fluids. 6 Protozoa are important causes of persistent diarrhea, 2 and current emphasis on rehydration fluid is adequate only for acute diarrhea agents such as rotavirus, which is self-limiting if the lost fluid and electrolytes are adequately replaced. These observations raise fundamental questions as to the quality of diagnosis and care provided to these children.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more than 90% of the disease burden is contributed by the developing world [5,6]. Each bout of diarrhea progressively compromises the immune system, indirectly killing many more millions each year [7].In Pakistan, rapid population growth, industrialization, and urbanization have stressed the water resources and compromised water quality, which subsequently negatively impacts children's school performance [8][9][10]. A recent study revealed that 21 million people in Pakistan are deprived of basic access to safe water [11].…”
mentioning
confidence: 99%
“…Furthermore, more than 90% of the disease burden is contributed by the developing world [5,6]. Each bout of diarrhea progressively compromises the immune system, indirectly killing many more millions each year [7].…”
mentioning
confidence: 99%